LG G5 Advertisement Focused on Visual and Verbal Image - Lee Seung Hwa (Institute of Research and Community Outreach - Petra Christian University, 2020)
I want to analyze LG G5 advertisement, because LG G5 is different from other companies’ mobile phones. When LG G5 was released newly, LG G5 had special functions, unique designs, and several additional device and modular types. Therefore, LG G5 advertisement is worth researching. This research attempts to discover the perceived meaning in G5’s advertisement of LG. At the elaborations of research problem, two research questions arise as follows (1) how meaning is in the advertisement created through verbal expression (2) how meaning is in the advertisement supported by visual expression. The theories used are semiotics, signification, denotation and connotation. Methods are descriptive qualitative. The findings imply that LG G5 is a symbol of happiness, enjoyment, and an icon of fancy and modernity by the verbal expression. In addition, this shows LG G5’s brand image as LG is technology innovation company, as well as a company that support happiness in people’s life by verbal and non-verbal expression.Keywords: Visual and verbal images, life, good, happiness, phone, modular type